2021
DOI: 10.3389/fpls.2021.691835
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Its Homologs Induce Immune Responses via Receptors trP47363-trP13076 in Nicotiana benthamiana

Abstract: Melatonin (N-acetyl-5-methoxytryptamine), a naturally occurring small molecule, can protect plants against abiotic stress after exogenous treatmenting with it. It is not known if melatonin homologs, such as 5-methoxytryptamine and 5-methoxyindole, that are easy and more cost-effective to synthesize can stimulate the plant immune system in the same manner as melatonin. In the present study, we assessed the biological activity of the melatonin homologs, 5-methoxytryptamin and 5-methoxyindole. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Bt can also directly promote plant growth by synthesizing phosphate lysing enzymes [ 60 ], siderophores [ 61 ], and plant hormones [ 62 , 63 ]. When analyzing the growth-promoting effects of GBAC46 and NMTD81 strains in rice, it was found that the selected strains significantly promoted rice physiological parameters such as root and shoot length [ 10 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bt can also directly promote plant growth by synthesizing phosphate lysing enzymes [ 60 ], siderophores [ 61 ], and plant hormones [ 62 , 63 ]. When analyzing the growth-promoting effects of GBAC46 and NMTD81 strains in rice, it was found that the selected strains significantly promoted rice physiological parameters such as root and shoot length [ 10 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies take the important stance that the transmembrane receptor of melatonin (PMTR1/CAND2) is found in Arabidopsis , tobacco, alfalfa, and maize [ 116 , 117 , 118 , 119 ]. It is also located in the plasma membrane, and can interact with G-protein α subunits, thereby activating RBOHs to promote stomatal closure in Arabidopsis ( Figure 2 ) [ 116 , 119 ].…”
Section: How Melatonin Directs With the Rboh-regulated Ros Signaling ...mentioning
confidence: 99%
“…The impacts of several melatonin homologs on disease resistance against P. nicotianae and stomatal closure were investigated in N. benthamiana. The results showed that the melatonin homolog 5-methoxyindole could induce plant immunity by inducing stomatal closure, similar to melatonin in N. benthamiana [29]. Then, to identify the fungicidal activity of various concentrations of melatonin and its homolog 5-methoxyindole against F. graminearum, water was used as a negative control and melatonin was used as a positive control.…”
Section: -Methoxyindole Displayed Strong Antagonistic Activity Against F Graminearum Ph-1 Similar To Melatoninmentioning
confidence: 99%
“…For example, phytomelatonin regulation of stomatal closure is dependent on its receptor CAND2/PMTR1-mediated H 2 O 2 and the Ca 2+ signaling transduction cascade after treatment with 10 µM melatonin [26], and 10 µM melatonin is responsible for rice resistance to rice stripe virus infection through a nitric oxide-dependent pathway [27]. Melatonin application reduces fluoride uptake and toxicity in rice seedlings by altering abscisic acid (ABA), gibberellin (GA), auxin, and antioxidant homeostasis after treatment with 20 and 100 µM melatonin, and its homologs induce immune responses via receptors trP47363-trP13076 in Nicotiana benthamiana [28,29].…”
Section: Introductionmentioning
confidence: 99%